Laura Gawlinski. The Athenian Agora Museum Guide - Newman, Alana N. (Journal of Greek Archaeology, 2017)
Between 1953 and 1956 the Hellenistic Stoa of Attalos was converted into a museum. It currently houses the finds from excavations carried out by the American School of Classical Studies in the Athenian agora since 1931. Laura Gawlinski’s The Athenian Agora Museum Guide is a well-written guidebook to this unique museum. The aim of this book is to provide the reader with supplementary historical, archaeological, and cultural information not only about the artefacts displayed in the museum, but also about the building itself. Indeed, Gawlinski makes a commendable effort to emphasise the distinct vantage point, that the visitor has to experience finds from the agora in a restored building from the ancient site.